Analysis Of The Utilization Of Echo Hiding Algorithm In Hiding Secret Messages - Pangaribuan, Cahaya Elyzabeth; Ogy Kevinta Surbakti; Fera Sihotang; Yosafat Tamba; Yordan Daniel Ndruru; Paskah Marto Hasugian (Sean Institute, 2024)
Steganography is a technique of hiding information in other media to maintain the confidentiality of the message. One of the challenges in steganography is finding a method that can insert data without being detected while maintaining the quality of the original media. This study discusses the application of the Echo Hiding algorithm in audio steganography, which utilizes acoustic properties to insert information into sound signals. The main objective of this study is to analyze the effectiveness and security of the Echo Hiding algorithm in hiding data in audio signals. To achieve this goal, this study uses a digital signal processing method, which includes the stages of message insertion, hidden message extraction, and audio quality evaluation using objective and subjective parameters. Testing was carried out with various scenarios to assess the capacity of insertion, resistance to attacks, and changes in sound quality. The results showed that the Echo Hiding algorithm was able to store information efficiently with little impact on audio quality. Signal analysis showed that the modifications made were not significant to the listener's perception, thus increasing the security and transparency aspects in audio steganography. Thus, this study contributes to the development of a safe and effective steganography method to maintain the confidentiality of information in sound media.